Assessment of risk factors and perceptions of noncommunicable diseases among adults in a rural area of West Bengal: A mixed method study - Soumik Roy; Shuvankar Mukherjee; Ajijul Laskar; Sukanata Majumdar; Manidipa Roy (Journal of Family Medicine and Primary Care)
Introduction: The burden of noncommunicable diseases (NCDs) like cardiovascular diseases, diabetes, hypertension, stroke, and cancers has been increasing in India. This rise of NCDs is mainly due to an increase in prevalence of various risk factors like tobacco use, alcohol intake, overweight, and physical inactivity. Objective: 1) To estimate the proportion of different NCDs among study subjects, 2) to identify association of NCDs with various risk factors if any, and 3) to assess perceptions regarding risk factors and curative aspects of NCDs. Materials and Methods: A mixed method study (quantitative ◊ qualitative) was done in Hariharpara Rural Hospital from September 26, 2023 to November 6, 2023, and quantitative data were collected using predesigned pretested semistructured schedules framed on the basis of WHO STEPS framework from 224 patients who were satisfying inclusion criteria by complete enumeration in NCD clinics. Data were analyzed with SPSS version 23.0, and binary logistic regression was done to identify association of NCDs with various risk factors. Qualitative exploration was conducted by focused group discussion to know their perceptions regarding risk factors and curative aspects of NCDs. Results: In this study, 60.26% were hypertensive, 30.35% were diabetic, and 16.51% had other noncommunicable diseases. The binary logistic regression model was done and found geriatric age group study subjects had 4.26 times more chances than their below counterparts and alcoholics had 3.21 times more chances than nonalcoholics of having hypertension, which were statistically significant. In the case of diabetes, geriatric study subjects had 3.19 times more chances of having diabetes than their below counterparts, which was statistically significant. Qualitative analysis revealed there was more inclination toward curative than preventive aspects of NCDs. Conclusion: The rise of NCDs was more among the geriatric age group and study subjects who were alcoholic. The perceptions of study subjects were inclined more toward curative than preventive aspects of NCDs.